Acid-etching effects in hypomineralized amelogenesis imperfecta. A microscopic and microanalytical study - Sánchez Quevedo, C. (2006)
Objectives: The purpose of this study was to use quantitative x-ray microprobe analysis with scanning electron microscopy to define the morphostructural and calcification patterns in the enamel of teeth with the hypomineralized variant of amelogenesis imperfecta. Study design: We compared 5 fragments of permanent human canines from patients with clinically diagnosed hypomineralized amelogenesis imperfecta and 5 normal permanent canines from subjects without amelogenesis imperfecta. All specimens were etched with phosphoric acid for morphological and microanalytical examination. Results: Two types of etching patterns were found; in addition, islets of pattern I were seen within areas of pattern II. Microanalysis detected no significant differences in calcium concentration between specimens with amelogenesis imperfecta and normal control specimens after acid etching. Pattern III was not observed. Conclusions: The changes and their distribution in the enamel structure after 30 s of acid etching are described in teeth with this rare disorder. Although these data seem to coincide with alterations in prism development, no alterations in calcium concentration were found.